Meningkatkan Kesejahteraan Masyarakat LMDH Wana Lestari Melalui Sosialisasi Potensi, Kesehatan, Dan Peluang Bisnis Tebu Hitam - Rico Yanuar Ardiansyah; Indah Rahayu Dwi Ningsih; Nurfarisa Yuristya; Taufik Setyadi (Lembaga Pengembangan Kinerja Dosen, 2024)
This outreach activity aims to educate the LMDH Wana Lestari regarding product innovation that can be used as a business opportunity through outreach about the potential, health and business opportunities of black sugar cane. Black sugar cane (Saccharum officinarum) has many benefits that are not widely known by the public, including health benefits and economic value. The method used in this research includes several stages as follows: 1) Preparation and development stages, 2) Activity implementation stages, 3) Evaluation and monitoring stages. The results of the research show that the outreach carried out was successful in increasing public understanding of the benefits of black sugar cane, both in terms of health and business opportunities. People are becoming more motivated to cultivate black sugar cane as an alternative source of income. It is hoped that the implementation of this program can contribute to improving the welfare of the LMDH Wana Lestari community in a sustainable manner.